2010
DOI: 10.2984/64.4.527
|View full text |Cite
|
Sign up to set email alerts
|

Can Ptilinopus greyii (Columbidae) Disperse Seeds in New Caledonia's Dry Forests?

Abstract: Conservation of endangered habitats of South Pacific islands is partially dependent on activity of seed dispersers. In consuming fruits, animals can spread seeds from parent plants to distant sites, thus contributing to plant regeneration and colonization of new sites. In the dry forests of New Caledonia, the red-bellied fruit-dove, Ptilinopus greyii, is a potential disperser of many fleshyfruited species. Trials with a captive bird showed that gut passage enhanced seed germination for Diospyros fasciculosa an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Very little is known about pollinators and fruit dispersal in these species; most species are dioecious and have fleshy fruits. The fruits of other Diospyros species present on the island are eaten by birds - for example, the fruits of D. fasciculosa (of similar size as the fruits in the radiating group) are dispersed by the red-bellied fruit-dove, Ptilinopus greyii (Tassin et al 2010). We assume the seeds of the radiating group are also dispersed by birds, but the genetic evidence is consistent with limited gene flow between populations.…”
Section: Discussionmentioning
confidence: 99%
“…Very little is known about pollinators and fruit dispersal in these species; most species are dioecious and have fleshy fruits. The fruits of other Diospyros species present on the island are eaten by birds - for example, the fruits of D. fasciculosa (of similar size as the fruits in the radiating group) are dispersed by the red-bellied fruit-dove, Ptilinopus greyii (Tassin et al 2010). We assume the seeds of the radiating group are also dispersed by birds, but the genetic evidence is consistent with limited gene flow between populations.…”
Section: Discussionmentioning
confidence: 99%
“…Smaller fruits (ca. \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$<$\end{document}2 cm) are consumed by more diminutive birds such as Sturnidae (Table 1; Tassin et al 2010), which probably move over short distances, but are able to shift between different vegetation types (Barré et al 2006). Finally, large grey or brown fruits having armed appendages are considered to be consumed by large geckos ( Rhacodactylus , Mniarogekko , and Correlophus genera) because they are not discouraged by the fruits’ repelling structures (Whitaker and Bauer, pers.…”
mentioning
confidence: 99%
“…Then seeds were quickly placed on water-wet cotton (humidity 100 %) in transparent Petri dishes. Four replicates of 25 seeds each (pooled from different individual plants and different individual animals) were tested for each treatment (Tassin et al 2010;De Carvalho-Ricardo et al 2014) except for R. exulans, for which very few seeds were obtained from the faeces (n = 12 for Ficus and n = 9 for Freycinetia). There were six ingested seed treatments: R. rattus, R. exulans, P. ornatus, P. tonganus, P. vetulus, and D. goliath.…”
Section: Germination Trialsmentioning
confidence: 99%
“…A study conducted on 123 new-Caledonian rainforest tree species revealed that 72 % have adaptations for dispersal by vertebrates (Carpenter et al 2003), and pinpointed the importance of conserving native frugivorous species to maintain dispersal processes of endemic plants. Native frugivores on New Caledonia's main island (Grande Terre) include 47 species of Squamata (42 gekkos and 5 skinks) (Hervé Jourdan, personal communication), 15 species of birds (Barré and Dutson 2000;Tassin et al 2010), and four species of flying foxes (Flannery 1995), and may have been more diversified before human and rat colonization (Balouet and Olson 1989;Balouet 1991).…”
Section: Introductionmentioning
confidence: 99%